Are the Scrub Women Rooting for You? - Hercules Incorporated (1941 Hercules Advertisements, 1941)
Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Disinfectants industry; Hercules Incorporated; Pine oil; Corporations; Naval stores; Disinfection and disinfectants; Advertising, Industrial